Genetic polymorphisms and novel allelic variants of CYP2C19 in the Chinese Han population. (November 2012) - Hu, Li-Ming; Dai, Da-Peng; Hu, Guo-Xin; Yang, Jie-Fu; Xu, Ren-Ai; Yang, Li-Ping; Qian, Jian-Chang; Ge, Ren-Shan; Cai, Jian-Ping
Aim: This study aims to systematically investigate the genetic polymorphisms of the CYP2C19 gene and provide accurate data of the allele distribution pattern in the Chinese Han population.Materials & Methods: We amplified all nine exons of the CYP2C19 gene in 2127 unrelated healthy Chinese Han subjects from two geographical locations (Zhejiang province, n = 1127; Hebei province, n = 1000), using direct sequencing.Results: In total, six previously reported alleles were found in our study, in which two alleles CYP2C19*6 and CYP2C19*18 were reported for the first time in Chinese Han subjects. In addition, 35 novel variants were detected in the present work, which included 11 new named alleles, 12 nonsynonymous mutations and one insert variant.Conclusion: This study provides important data on the pattern of CYP2C19 polymorphisms in Chinese Han subjects, using the largest group of individuals. Furthermore, the study also detects the largest number of novel alleles in one population. These findings are of potential benefit to the development of personalized medicine for the Chinese Han population. Original submitted 25 June 2012; Revision submitted 20 August 2012